ACTIVE DYNAMICS OF THE ENZYMES OF THE ANTIRADICAL PROTECTION AND THE GENERAL ANTIOXIDATIVE ACTIVITY BY THE DEVELOPMENT OF THE EXPERIMENTAL ISCHEMIC REPERFUSION OF LIVER - K A Popov; I M Bykov; G A Ermakova; I Y Tsymbalyuk (RUDN Journal of Medicine, 2018)
The purpose of the study: to research the active changes in several enzymes of the antioxidative protection within the dynamical development of the liver reperfusion in rats. Materials and methods: the study has been performed on 95 white non-lineal male rats with the mass of 240-280 g divided into groups, the biological material of which has been sampled within 5-20 minutes of the ischemic period and 5-20 minutes of the reperfusion period with the interval of 5 minutes. To evaluate the changes of the antioxidative system the activity of the superoxide dismutase, the erythrocyte catalase and the liver homogenate as well as the general antioxidative activity have been determined. Results: the performed study has demonstrated the imbalance development for the relation between the activity of catalase and superoxide dismutase by the development of the ischemic reperfusion syndrome with the change of this relation to the prevalence of the catalase activity on the systemic level and the superoxide dismutase activity on the organic level after the circulatory restoration. Besides the increase in activity of the studied enzymes from the erythrocyte, meal by 2 times in comparison with the control group has been determined especially at the ischemic period as well as the tendencies to the progressive activity decrease of the same enzymes in the liver tissue. The general antioxidative activity in the period of ischemic reperfusion has been decreasing to the fifth minute of ischemia by 2 times and has lasted on the same level (0.04-0.05 mg/l of vitamin C in terms of 1 gram of homogenate protein) during the entire experiment. Conclusion: the received results have demonstrated the possibility for the evaluation of the functional state for the system of oxidative restorative homeostasis in an animal by ischemic reperfusion of the liver against the background of the lowered general antioxidative activity. It was marked also the necessity of the metabolic support of this link within the system of non-specific resistance for the correction of the developing disorders.